Generic green skills development: initiatives of green manufacturing industries in Johor, Malaysia - Abd. Hamid, Mohd. Zolkifli (American Scientific Publishers, 2018)
As green economy continues to evolve, the catchword ‘generic green skills’ has gained widespread attention among occupational associations, industries, businesses and sector councils. To respond effectively to the shift for a greener economy, industries have initiated steps to train workers for green practices. This study seeks to examine how the green manufacturing industries in Johor, Malaysia inculcate generic green skills among workers. Qualitative approach by means of interview was used which involved four middle management personnel from four different industries. Out of seven areas of initiative implemented by the companies, two were considered prominent based on the activities adopted, that is in-house training (94.0%) and environmental culture programs (93.75%), while retraining (50.0%) and skills building (31.25%) were the least implemented.